Association between extremely high-density lipoprotein cholesterol and adverse cardiovascular outcomes: a systematic review and meta-analysis - Zhang, Guanwei; Guo, Jiajuan; Jin, Hongguang; Wei, Xiaojing; Zhu, Xing; Jia, Weitao; Huang, Yongsheng (Frontiers in Cardiovascular Medicine, 2023)
Background The association between high-density lipoprotein cholesterol (HDL-C) and adverse cardiovascular outcomes is understudied. Based on cohort studies, the current study aimed to investigate the association of extremely high HDL-C with all-cause, atherosclerotic cardiovascular disease (CVD) mortality, and stroke risk. Methods A systematic literature search in Embase, PubMed, Cochrane Library, and Web of Science was performed to collect relevant cohort studies published before August 20, 2022. A random-effects model was used to pool relative risks (RRs) and 95% confidence intervals (CIs). Results A total of 17 cohort studies involving 19,630,829 participants were included, encompassing 18,547,132 total deaths (1,328,036 CVD deaths). All-cause mortality, CVD mortality, and stroke risk in the extremely high HDL-C group were increased by 15% (RR = 1.15, 95% CI:1.05–1.25), 14% (RR = 1.14, 95% CI:0.96–1.35) and 14% (RR = 1.14, 95% CI:0.82–1.58), compared to the normal HDL-C group. In subgroup analyses, extremely high HDL-C was associated with a reduced risk of CVD mortality in women and a lower risk of stroke in men compared to normal HDL-C levels. Conclusions The extremely high levels of HDL-C were associated with elevated risks of all-cause mortality, CVD mortality, and stroke. More well-designed studies are needed to confirm our findings. Systematic Review Registration https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=370201, identifier: CRD42022370201.